Iconic languages: Towards end-user programming of mobile applications. (February 2017) - Francese, Rita; Risi, Michele; Tortora, Genoveffa
Abstract: After tracing the steps that led to the current generation of iconic languages starting from the original idea of S.K. Chang, we describe an iconic language, named MicroApp, for modeling pervasive mobile applications directly on the mobile device. MicroApp exploits generalized icons for composing mobile applications: services are represented by icons and are composed of adopting colors for representing data-flow. We also qualitatively evaluate the visual environment that implements this iconic language.